Preventive Maintenance and Financial Performance: Serial Mediation of OEE and Productivity in the Paper Industry - Oviyan Patra; Firman Pratama; Evan Nugraha (Politeknik Siber Cerdika Internasional, 2026)
Background: The pulp and paper industry is capital-intensive and operates continuously, making equipment availability a critical determinant of corporate performance. Preventive maintenance is often regarded merely as a cost center, despite its significant potential as a strategic value-creating activity. Objective: This study aims to analyze the influence of preventive maintenance on the financial performance of PT Indah Kiat Pulp and Paper Serang Mill through the serial mediation of Overall Equipment Effectiveness (OEE) and paper machine productivity, offering a novel chain-mediation framework that connects maintenance activities to corporate financial outcomes. Methods: A quantitative approach was employed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS, based on data from 120 internal respondents collected through a five-point Likert-scale questionnaire and triangulated with company operational and financial data. Results: All six hypotheses are statistically supported. Preventive maintenance positively affects OEE (β = 0.570); OEE affects productivity (β = 0.601); and productivity affects financial performance (β = 0.514). Serial mediation is confirmed: OEE mediates preventive maintenance → productivity, while productivity mediates OEE → financial performance. Full serial mediation yields an indirect effect of 0.176. Conclusion: These findings confirm a complete value-creation chain through a novel serial mediation model (preventive maintenance → OEE → productivity → financial performance), extending maintenance management theory by repositioning preventive maintenance as a strategic mechanism for sustainable corporate value creation in capital-intensive manufacturing industries.